From Neophyte to Non-White: Moral Theology and Race Mixture in Colonial Brazil - Hill, Ruth (Journal of Early Modern Christianity, 2017)
The first global debate about racial admixture originated in the exegesis of papal privileges designed to aid Catholic converts in Spanish and Portuguese Asia, Africa, and the Americas. Later Scholastics contributed to the ontology of race by aligning religious status with origins, or blood, in ways that departed from raging controversies around Jewish and Muslim converts to Catholicism. Through recourse to seventeenth-century probabilism, these moral theologians and canonists debated the meaning of the term mestizos , a Spanish term that appeared alongside the Latin mixtim progeniti ("mixed offspring") in marriage privileges granted to neophytes in colonial contexts. Were persons with 25% of non-European blood mestizos , or, instead, Europeans? Were mulattos, as mixtim progeniti, mestizos also? The mestizo conundrum, and the opinions and papal bulls that it generated, shaped legal constructions of whitening (Spanish blanqueamiento , Portuguese branqueamento ) in colonial Latin America, and anticipated the moral and legal dilemmas of Brazil’s present-day affirmative-action program.